Strengthened microstructure and mechanical properties of austenitic 316L stainless steels by grain refinement and solute segregation - Yurong Wang; Buwei Xiao; Xiaoyu Liang; Huabei Peng; Jun Zhou; Feng Lin (Journal of Materials Research and Technology)
Strengthening conventional materials through additive manufacturing is generally understood to occur due to rapid cooling in the metallurgical process, which refines the microstructure by producing smaller grain sizes and segregating elements at specific locations. However, the effectiveness of this enhancement mechanism for increasing strength or elongation of parts depends significantly on the nature of the material. For example, austenitic 316L stainless steel fabricated by laser powder bed fusion exhibits superior ductility but struggles to improve its strength. In order to explore the contribution of grain scales and solute segregation in the strengthening of rapid solidification microstructures during additive manufacturing, we investigate an austenitic 316L stainless steel micro-alloyed with Nb and Ti. The austenitic stainless steel is strengthened through grain size refinement and the presence of dislocation cell boundaries enriched with Nb/Cr phases, leading to yield and tensile strengths exceeding 0.8 GPa and 1.1 GPa, respectively. Its strength exceeds that of most current additively manufactured austenitic stainless steels. The strong ferrite-forming components (Nb and Ti) contribute significantly to the microstructural refinement of austenitic stainless steels, with the average grain size decreased by 65.4% compared to austenitic 316L stainless steel. Additionally, the fine grains exhibit predominantly high-angle grain boundaries, and the elevated density of solute segregation in these regions plays a crucial role in contributing to exceptional strength of materials.